The Influence of Design and Technological Parameters on the MAF Process - Shather, Saad kariem; Mousa, Shakir M. (Al-Khwarizmi Engineering Journal, 2015)
Abstract Experimental work from Magnetic Abrasive Finishing (MAF) tests was carried out design parameters (amplitude, and number of cycle which are formed the shape of electromagnetic pole), and technological parameters (current, cutting speed, working gap, and finishing time) all have an influence on the mechanical properties of the surface layer in MAF process. This research has made to study the effect of design and technological parameters on the surface roughness (Ra), micro hardness (Hv) and material removal (MR) in working zone. A set of experimental tests has been planned using response surface methodology according to Taguchi matrix (36) with three levels and six factors. The analysis of variance and instruction curves indicate some significant. X1; X4; X6 have a significant effect on the surface roughness Ra for steel, X2 has mildly significant, while X3 and X5 have insignificant effect. The results showed that roughness of workpiece decreased from 0.3 to 0.15 µm that means improved the roughness to 100%. Keywords: Design and technological parameters, micro-hardness, surface roughness, material of removal, MINITAB software.